Evidenz der Prophylaxebehandlung bei erwachsenen Hämophilen - Beck, K.-H.; Holzschuh, J. (Hämostaseologie, 2011)
In contrast to children with haemophilia the scientific evidence of prophylaxis treatment in adults is not yet proven. Existing studies are of observational character and mostly retrospectively designed. Therefore, opinion leaders in this field postulate prospectively designed, randomized, controlled and multicentric studies to set up urgently needed guidelines. Evidence according to the Canadian task force ranking is assessed as level III with a re- commendation grade C by the authors.The recognition of benefits of health care providers in accordance with the German Federal Joint Committee generally demands a Grade- Ia to Ib evidence. As long as the actual evidence of prophylaxis in adult haemophiliacs does not meet the postulated criteria of the German Federal Joint Committee, prophylactic replacement therapy of the individual case has to be well documented and reasonably explained.
Keywords: Replacement therapy; adult haemophiliacs; primary and secondary prophylaxis